Online Education for Sustainable Development: An Analysis of Test Scores of Tertiary Sri Lankan ESL Learners in Onsite Summative and Online Summative Examinations - Udara, N.; Fairooz, F.; Jayasundara, A. (NSBM Green University, 2022)
The present study is a quantitative study which aims to analyse online summative written examinations and its effectiveness against the onsite summative written examinations. When the entire planet faced COVID-19 pandemic, the education system in Sri Lanka was on hold for a considerable period. As a result, online examinations or computer-based language tests became a popular testing method to continue education amidst all the challenges. Multiple higher education institutes (both state and private) have implemented online exams to assess the students’ language skills. Thus, 42 second year students were selected from the Department of Human Resource Management, University of Kelaniya who follows a compulsory English module; Advance English for Commerce and Management studies. Their scores at two different examinations (online and onsite) were analysed using the SPSS. The present study is based on concurrent validation, which focuses on the degree of equivalence between two test scores. The result of the analysis proves that online tests are more valid and relevant than the onsite tests as there is a significant gap between the scores of the online examination and onsite examination. The analysis further proves that the students have outperformed in online examination whereas scores of onsite test fall onto regular distribution around a single mean. The findings of this study will be of significant value to ESL (English as a Second Language)academics and students who learn English as a Second Language. The findings problematize the effectiveness of onsite examinations as a successful language evaluation method even though it is the conventional and the most used method of language testing in Sri Lanka.
Keywords: : language testing; online examinations; onsite examinations validity; relevance; test scores